Dari Spiritual hingga Imajinasi yang Diperbarui: Pencarian C. S. Lewis akan Sukacita, Imajinasi, dan Tuhan - Imbert, Yannick (STT Reformed Injili Internasional, 2024)
The conversion of C. S. Lewis to Christian theism weaves together his quest for joy and his evolving view on the power of imagination. Lewis' acceptance of Christianity raises questions about the nature of the relationship between these two fundamental elements of his philosophical evolution: joy and imagination. In this article, we aim to clarify this aspect of Lewis' intellectual and spiritual life by considering his philosophical development. The essential relationship between joy and imagination becomes clear only if we consider Lewis' intellectual journey from Atheism to Idealism and then to Christian theism. In this article, we consider Lewis' intellectual development from the moment he adopted his own version of subjective idealism.